Measuring financial performance of going public companies of oil & gas industry during the period of before and after 2010s oil glut phenomenon in 2010-2016 - Andriana, Putri; Daryanto, Wiwiek M. (The Indonesian Journal of Business Administration, 2018)
Abstract - Energy is one of the most important commodities in the world. This is proven by the increasing of total world’s production and consumption of crude oil every year. The supply of crude oil started to exceed 0.6 million barrels in 2014 and keep going until 2016 (Annual Report of OPEC, 2016) then, it led the world to 2010s Oil Glut. Unfortunately, 2010s Oil Glut caused the falling back of world’s crude oil prices. This research aims to measure, analyze, and compare the financial performance of Public Listed Oil and Gas Companies in Indonesia namely PT Medco Energi Internasional Tbk. (MEDC), PT Energi Mega Persada Tbk. (ENRG), and PT Benakat Integra Tbk. (BIPI) from 2010 to 2016. This research uses financial ratios such as Return on Assets (ROA), Total Debt to Total Assets (TDTA), and Total Assets Turnover (TATO) and also uses paired t-test to verify the differences of financial ratios during the period of before (2010-2012) and after (2014-2016) 2010s oil glut. The results of this study show that the ROA value of MEDC was positive, but for ENRG and BIPI were negative. Moreover, the TDTA of the companies were high which above 60 percent. MEDC has accepted the alternate hypotheses for ROA and TDTA variables with paired t-test results 0.018 and 0.042 respectively. Meanwhile, ENRG has accepted the alternate hypotheses for TATO variable with paired t-test results 0.017. And lastly, BIPI has accepted the alternate hypotheses for TDTA and TATO variables with paired t-test results 0.026 and 0.036 respectively. Author recommends the companies for doing assets management and controlling the amount of debt to be taken during 2010s Oil Glut Phenomenon in order to survive in this situation.Keywords: 2010s Oil Glut, Financial Ratios, Paired T-Test